2006
DOI: 10.1007/s11130-006-0003-y
|View full text |Cite
|
Sign up to set email alerts
|

Physical Quality and Carotene Content of Solar-Dried Green Leafy and Yellow Succulent Vegetables

Abstract: The effects of vegetable type, vegetable dimensions, and solar drier load on dehydration rate; and texture, color, water activity, and carotene content of solar-dried carrots, sweet potatoes, and collard greens were studied. Mean dehydration rates (moisture loss,%/hr) for solar dried loads of 430 g/m2 and 715 g/m2 were 3.3 +/- 0.30% and 3.8 +/- 0.20% for carrots and sweet potatoes, respectively. Loads of 360 g/m2 and 465 g/m2 of collard greens had dehydration rates of 6.3 +/- 0.10% moisture loss per hr. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
(59 reference statements)
1
13
0
Order By: Relevance
“…Bengtsson et al, 2008 suggested that for an equivalent drying time, cultivars with higher moisture content and with higher initial carotenoid content tended to lose more carotenoids during the drying process. Mdziniso et al, 2006, also observed that sweet potato exhibited the least b-carotene loss (5-6% dry basis) whereas carrots exhibited the highest (49-68%), and their respective fresh moisture contents were 76 and 91%.…”
Section: The Effect Of Processing and Storage On Carotenoid Retentionmentioning
confidence: 80%
See 2 more Smart Citations
“…Bengtsson et al, 2008 suggested that for an equivalent drying time, cultivars with higher moisture content and with higher initial carotenoid content tended to lose more carotenoids during the drying process. Mdziniso et al, 2006, also observed that sweet potato exhibited the least b-carotene loss (5-6% dry basis) whereas carrots exhibited the highest (49-68%), and their respective fresh moisture contents were 76 and 91%.…”
Section: The Effect Of Processing and Storage On Carotenoid Retentionmentioning
confidence: 80%
“…Solar drying is achieved by direct sun radiation on the material covering the solar dryer, reaching internally higher temperatures, and similar or slightly lower humidity as the outside environment. The pVAC retention in sweet potato ranged from 77 to 96% after solar-drying (Mdziniso et al, 2006, Bengtsson et al, 2008, Bechoff et al, 2009, Bechoff et al, 2010a, and Bechoff et al, 2011a. In three studies, the pVAC retention from solar-drying was not significantly (p < 0.05) different from sun-drying (Bengtsson et al, 2008, Bechoff et al, 2009, Bechoff et al, 2010a.…”
Section: Sweet Potatomentioning
confidence: 88%
See 1 more Smart Citation
“…They concluded that blanching prevented non-enzymatic browning reaction, which resulted in a relatively high value of total carotenoids and b-carotene content, as well as redness and yellowness. Steam blanching also provided good results when applied to collard greens, which retained 55-98 % of b-carotene [57]. Artichoke byproducts Ohmic blanching was the fastest method to inactivate the peroxidase enzyme at 85°C and provided higher vitamin C and total phenolic content retention than water blanching [36] Blanching (i) Ohmic blanching (ii) (i) Water at 85 and 100°C, 120-600 s (ii) Voltage gradients of 24, V/cm, at 80°C, 0-300 s Artichoke heads Heating allowed quick and uniform heating of food product and was beneficial in terms of enzyme inactivation, colour; higher total protein and polyphenolic content in ohmically blanched samples [29] Osmotic Using lower blanching temperatures is another approach to minimizing nutrients decrease.…”
Section: Blanchingmentioning
confidence: 96%
“…It usually employs water or steam at high temperatures for a short period of time. If applied under optimal conditions, blanching may improve the colour, flavour, texture, nutritional quality and overall acceptability of dried vegetables [57]. However, significant reductions in the levels of nutrients caused by blanching were reported by several authors.…”
Section: Blanchingmentioning
confidence: 99%